Inwardly rectifying potassium channels influence Drosophila wing morphogenesis by regulating Dpp release. - Dahal, G.R.; Pradhan, S.J.; Bates, E.A. (Development, 2017)
Loss of embryonic ion channel function leads to morphological defects, but the underlying reason for these defects remains elusive. Here, we show that inwardly rectifying potassium (Irk) channels regulate release of the Drosophila bone morphogenetic protein Dpp in the developing fly wing and that this is necessary for developmental signaling. Inhibition of Irk channels decreases the incidence of distinct Dpp-GFP release events above baseline fluorescence while leading to a broader distribution of Dpp-GFP. Work by others in different cell types has shown that Irk channels regulate peptide release by modulating membrane potential and calcium levels. We found calcium transients in the developing wing, and inhibition of Irk channels reduces the duration and amplitude of calcium transients. Depolarization with high extracellular potassium evokes Dpp release. Taken together, our data implicate Irk channels as a requirement for regulated release of Dpp, highlighting the importance of the temporal pattern of Dpp presentation for morphogenesis of the wing.